Development of Density Meter Learning Media Using Arduino Uno to Improve Critical Thinking Abilities - Matsun; Adi Pramuda; Soka Hadiati; Hendrik Pratama (Postgraduate, University of Mataram, 2023)
This research aims to develop an Arduino Uno-based learning media that focuses on measuring the density of substances, with the aim of determining the suitability of the density meter, the accuracy of the density meter and improving students' critical thinking skills. The research method used is Research and Development (R&D) with a Four-D model with the steps Define, Design, Develop and Disseminate. This learning media is designed to provide students with practical experience in understanding the concept of density through direct experiments using a density meter connected to an Arduino Uno. Apart from that, this media is also designed to encourage students to develop critical thinking skills, such as analysis, evaluation and problem solving skills through reflective questions that are integrated into learning. Validation and testing are carried out through certain stages to ensure the quality and effectiveness of this learning media. Assessments are carried out on aspects of clarity of instructions, relevance to lesson material, appropriateness of level of difficulty, and impact on students' critical thinking abilities. The collected data was analyzed quantitatively and qualitatively. The results of the development of the density meter tool show that the assessment of expertsÂ is in the very appropriate category with a score of 90.50. The tool's accuracy results are an average of 99.55%. Apart from that, the post-test results revealed that the density meter was proven to be effective in improving students' critical thinking skills with an N-Gain value of 0.80 in the high category. It is hoped that the results of this research can make a positive contribution in the development of learning media that focuses on practical aspects and critical thinking skills. It is hoped that the Density Meter learning media using Arduino Uno can help teachers teach density concepts with a more interesting and effective approach, as well as encourage students to think more critically in understanding and applying science concepts in everyday life.